Dose–response association between fluid overload and in-hospital mortality in critically ill patients: a multicentre, prospective, observational cohort study - Wei Li; Bin Du; Yan He; Li Jiang; Guangxu Liu; Meiping Wang; Jing Wen; Wen Li; Bo Zhu; Ying Wen; Xiuming Xi (BMJ Open)
Objectives Fluid management is important in ensuring haemodynamic stability in critically ill patients, but can easily lead to fluid overload (FO). However, the optimal fluid balance plot or range for critically ill patients is unknown. This study aimed to explore the dose–response relationship between FO and in-hospital mortality in critically ill patients.Design Multicentre, prospective, observational study.Setting Eighteen intensive care units (ICUs) of 16 tertiary hospitals in China.Participants Critically ill patients in the ICU for more than 3 days.Primary outcome measures and analyses FO was defined as the ratio of the cumulative fluid balance (L) and initial body weight (kg) on ICU admission, expressed as a percentage. Maximum FO was defined as the peak value of FO during the first 3 days of ICU admission. Logistic regression models with restricted cubic splines were used to explore the pattern and magnitude of the association between maximum FO and risk of in-hospital mortality. Age, sex, Acute Physiology and Chronic Health Evaluation II score, Sequential Organ Failure Assessment score on admission, main diagnosis on admission to ICU, comorbidities, time of maximum FO, mechanical ventilation, renal replacement therapy, use of vasopressors and centres were adjusted in multivariable analysis.Results A total of 3850 patients were included in the study, 929 (24.1%) of whom died in the hospital. For each 1% L/kg increase in maximum FO, the risk of in-hospital mortality increased by 4% (adjusted HR (aHR) 1.04, 95% CI 1.03 to 1.05, p<0.001). A maximum FO greater than 10% was associated with a 44% increased HR of in-hospital mortality compared with an FO less than 5% (aHR 1.44, 95% CI 1.27 to 1.67). Notably, we found a non-linear dose–response association between maximum FO and in-hospital mortality.Conclusions Both higher and negative fluid balance levels were associated with an increased risk of in-hospital mortality in critically ill patients.Trial registration number ChiCTR-ECH-13003934.